STUDY REGARDING THE CORRELATION BETWEEN NEUROPSYCHOLOGICAL TESTS AND WEIGHT IN NORMAL PSYCHOMOTOR DEVELOPING OF THE PREMATURE BABIES - Hodorca Raluca; Onose Ionut (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Premature is a newborn alive whose birth weight is equal to or less than 2500 grams, regardless of the duration of gestation. Prematurity have sometimes negative effects on child development by slowing the psychomotor development (child goes to talk later), you can recover delay until the age of 3-5 years. Some of these older children, will be clumsy. PURPOSE: To verify the importance of the adapted recovery program making a correlation between neuro-psychological assessment tests and weight of children born prematurely. HYPOTHESIS: Early systematic and continuous intervention, using adapted physical therapy methods lead to a improved neuromotor development of the premature by reaching the normal range. MATERIAL AND METHODS The study included 10 children, 6 boys and 4 girls, born prematurely. They were subjected to the test "assessment of neuro-psychological development in children 0-36 months" (it is a battery of tests that help to evaluate their development monthly) and test weight. Applied therapeutic program included: exercise (performed by the game), massage, neuromotor rehabilitation methods (Bobath, Vojta, Kabat), hydrotherapy and music therapy. RESULTS AND DISCUSSION: If neuro-psychological tests, we proceeded to calculate averages scores for the 3 test, which is further correlated with children's weight. Average scores range between 7 and 10. 333, with an overall average of 9.371. In all 3 tests averages ranging from 8,575 in the initial stage, in 9386, and 10,152 in the midway point in the final stage. CONCLUSIONS: Weight, explain in smaller proportions, and other parameters and results of neuro-psychological tests children (65.6%). ANOVA models indicate statistically significant relationships between parameters and neuro-psychological testing stages, showing progressive improvement of children's performance. Following statistical interpretation can confirm the effectiveness of the recovery program implemented so we suggest to the parents and professionals in the field to start and continue adapted recovery program on the patients.